E-Bupot unification as a one-stop tax application: Just-in-time implementation in the public sector - Alaika, Abdullah Aziz; Biswan, Ali Tafriji (WIM Solusi Prima, 2025)
Digital transformation in tax administration is a strategic component of Indonesia’s ongoing bureaucratic reform, particularly in pursuit of improvements in the Ease of Doing Business (EoDB) index published by the World Bank. One of the key innovations introduced by the Directorate General of Taxes (DGT) is the e-Bupot Unification application—a one-stop platform that streamlines the preparation of tax withholding documents, tax calculation, and monthly income tax return (SPT Masa PPh) reporting. This study aims to analyze the implementation of Just-in-Time (JIT) principles within the e-Bupot Unification system and examine its impact on operational efficiency and the quality of public tax services at KPP Pratama Sanggau. Employing a qualitative case study approach, data were collected through interviews and direct field observations. The findings indicate that the e-Bupot Unification application aligns with five out of the six core principles of JIT: pull system, waste elimination, smooth workflow, total quality management, and top management commitment. The implementation significantly reduces the consultation time for taxpayers, eliminates redundant processes, and replaces the previously fragmented e-SPT systems. Moreover, the application functions as a form of cellular manufacturing within the public service context, thereby enhancing business process efficiency and improving taxpayer satisfaction. This study confirms that JIT is not solely applicable to manufacturing sectors but is also improvable in optimizing digital public service delivery in tax administration.